The Clinicopathological Characteristics and Prognoses of dMMR Gastric Adenocarcinoma Patients. (9th December 2021) - Wang, Jie; Xi, Yanfeng; Zhao, Jian; Rong, Xuetong; Lu, Weidong; Wang, Yusheng
Abstract : Background . Few studies on the clinicopathological features and prognosis of DNA mismatch repair deficiency (dMMR) gastric cancer (GC) have been reported, and no clear conclusions have been drawn about the factors affecting the prognosis of dMMR GC. The aim of this study was to explore the clinicopathological characteristics and prognoses of dMMR GC patients. Methods . From May 2011 to November 2020, GC patients who underwent surgery with dMMR confirmed by immunohistochemistry (IHC) at the Affiliated Cancer Hospital of Shanxi Medical University were selected. The patients' clinical and pathological data were collected. The recurrence-free survival (RFS) and overall survival (OS) rates of the patients were determined through follow-up. SPSS 26.0 was used to analyze the patients' clinicopathological features and prognoses. Results . A total of 162 dMMR GC patients met the inclusion criteria, and the median age was 63.5 years (32–89 years). dMMR GC was more common in males (65% vs. 35%), and most of the cases were stage II (the prevalence of stage I was 22%, that of stage II was 43%, that of stage III was 30%, and that of stage IV was 5%). Most of the lesions were located in the antrum (49%), followed by the cardia (25%). PMS2 and MLH1 (57%) deficiency was most common. Kaplan–Meier analysis showed that factors related to OS were family history (P = 0.048 ), number of lymph node (LN) metastases (P < 0.001 ), vascular tumor thrombus (P < 0.001 ), HER2 expression status (P = 0.025 ), and clinical stage (P < 0.001 ). The factors related to RFS included vascular tumor thrombus (P < 0.001 ), number of LN metastases (P < 0.001 ), and clinical stage (P < 0.001 ). Conclusion . In this study, dMMR GC was more common in men, and the median age was 63.5 years. Most of the lesions were in the antrum and showed the combined deletion of MLH1 and PMS2. dMMR GC patients tended to be early stage, and the prognosis of those with early-stage GC was better. dMMR GC patients with vascular tumor thrombus or >6 LN metastases had a high recurrence rate and poor survival outcome.